Hirelink: A Web Based Campus Recruitment Platform (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Traditional campus recruitment processes in educational institutions often involve manual coordination, spreadsheet management, and repetitive communication between students, recruiters, and placement officers. These practices lead to inefficiencies, delays, data inconsistency, and lack of transparency in recruitment activities. This paper presents HireLink, an intelligent AI-assisted web-based campus recruitment and placement management platform designed to automate and optimize the end-to-end recruitment workflow. The proposed system integrates student profile management, AI-based resume screening using Applicant Tracking System (ATS) scoring, recruiter job management, round-wise selection tracking, analytics dashboards, and alumni networking features within a centralized platform. The system is developed using React.js for the frontend, Django for backend processing, and MySQL for secure data management. Additionally, the platform incorporates automated eligibility filtering and resume ranking techniques to improve recruitment efficiency and decision-making. Experimental evaluation demonstrates significant reduction in administrative workload, faster candidate shortlisting, and improved operational transparency compared to traditional placement methods. The proposed platform provides a scalable, secure, and efficient solution for modern campus recruitment ecosystems.